Demensia Alzheimer pada Lansia - Nadhifa, Farin; Ramadhian, Muhammad Ricky; Nareswari, Shinta (Medula, 2024)
Alzheimer’s dementia in the elderly is a health problem that affects the quality of life of patients and their families. This study aims to explore the risk factors, prevention, and management of Alzheimer's Dementia in the elderly, focusing on the use of information technology for early detection, and the impact of physical activity as a preventive strategy. This research utilizes a literature review method by analyzing previous studies related to Alzheimer's dementia in the elderly. The analysis includes risk factors for dementia, prevention through physical activity, and the role of information technology in early detection and disease management. The results of the literature review indicate that the risk factors for Alzheimer's dementia in the elderly include age, genetics, and lifestyle. The study also shows that physical activity has a positive effect in reducing the risk of dementia. Moreover, information technology has significant potential in aiding early detection and disease management, allowing for more timely and effective intervention. Alzheimer’s dementia in the elderly requires a comprehensive approach involving early detection, prevention, and disease management. Physical activity and the use of information technology play vital roles in preventive and therapeutic strategies for Alzheimer's dementia.